Laura Pfuntner, Urbanism and Empire in Roman Sicily - Karambinis, Michalis (Journal of Greek Archaeology, 2021)
Roman rule signalled radical changes in the urban systems of the Mediterranean. More complex is the understanding of the restructuring that occurred in the Greek speaking lands, where a dense network of poleis existed already since the Archaic period. In the province of Achaia, although the basic elements of its Classical past were maintained (e.g., a modular urban system with hundreds of self-governing poleis which were sustained mainly by surpluses produced in their territories), in the Roman period this area was characterized by a significantly smaller number of cities and rural sites, in respect to pre-Roman times. Of great importance was the establishment of a few highly-centralized administrative centres of free or colonial status and economically privileged, that now became the focus of Roman administration and wealth. The majority of minor centres had from now on a marginal role, and many of them remained completely outside the new economic system.